Pengaruh Sosial-Budaya Akademik terhadap Kesadaran Beragama: Implikasi terhadap Konseling Religius di Perguruan Tinggi - Wahidin Wahidin; Muhamad Rozikan; Dina Fatma Septiani (Institut Agama Islam Neegri Madura, 2022)
Islamic Higher Education has a specific goal, namely instilling Islamic values ​​in the learning process, so that a strong religious awareness grows for students. Religious awareness is defined as a sense of religion, divine experience, faith which is manifested in attitudes and behavior. This study aims to describe the influence of the social environment and academic culture on students' religious awareness and its implications for religious counseling in higher education. The research method used is correlational with regression analysis techniques. The respondents of this study were students of the Tarbiyah and Teacher Training Faculty of IAIN Salatiga, with a total sample of 171 people. The results showed that the social environment and academic culture together had a positive effect on religious awareness. Based on the findings, the implications for religious guidance and counseling require a comprehensive approach to fully empower the potential of students